2018
DOI: 10.1016/j.jallcom.2018.05.318
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation stability and micro-property of (Nb, Ti)C carbides in MMC coating

Abstract: Multiple particles reinforced composite coatings have been noticed by many researchers due to its excellent wear resistance. In this work, (Nb,Ti)C multiple carbide reinforced Fe matrix composite coating was prepared. The microstructure and phase structure of the coatings were analyzed by scanning electron microscope (SEM) equipped with an energy-dispersive spectroscopy (EDS), X-ray diffractometer (XRD) and transmission electron microscopy (TEM). The stability, mechanical parameters (Elastic modulus, Bulk modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The average amount of primary carbide in the coatings is about 0.35, 0.48 and 0.53 per square micron, respectively. The Gibbs free energy of TiC is lower than that of NbC [6,30], and the element Ti is believed to improve the precipitation ability of primary NbC carbide [8], therefore the amount of primary carbides are increased with the increase of Ti contents. However, the increase in the amount of primary carbides will decrease the content of elements Nb, Ti and C in the molten pool, which may be the reason why the size of carbides are decreased with the increase of Ti content.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average amount of primary carbide in the coatings is about 0.35, 0.48 and 0.53 per square micron, respectively. The Gibbs free energy of TiC is lower than that of NbC [6,30], and the element Ti is believed to improve the precipitation ability of primary NbC carbide [8], therefore the amount of primary carbides are increased with the increase of Ti contents. However, the increase in the amount of primary carbides will decrease the content of elements Nb, Ti and C in the molten pool, which may be the reason why the size of carbides are decreased with the increase of Ti content.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Based on our previous work, the matrix in the coatings is the martensite (α-Fe), and the carbide are mainly connected with α-Fe, therefore, (Nb,Ti)C/α-Fe interface was selected in this work. The element compositions of (Nb,Ti)C carbide have been reported [7,8], in which, element Ti is rich in the core area of the carbide and element Nb is rich in the part of carbide near the matrix. Therefore, the combination of (Nb,Ti)C with α-Fe was calculated using the interface model of Nb0.75Ti0.25C with α-Fe.…”
Section: Interface Model and Adhesion Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies [12] have investigated the strengthening mechanism of (Nb, Ti)C carbide composite coatings, and we found that the addition of Ti can increase the hardness of carbides, reduce the mismatch between them and the matrix, and promote the formation of primary granular carbides, which are beneficial to the wear resistance of coating. Elements V, Mo, W and Cr are also MC type carbide forming ones, and their formation ability are weaker than that of Nb.…”
Section: Introductionmentioning
confidence: 97%
“…This definition describes an ideal composite material with a perfect structure. Real composite materials generally have imperfect structures-composite materials contain various defects [1,2,[4][5][6][7][8][9][10][11][12], especially when considering cast composites. Castings feature a specific structure that is related to the course of the manufacturing process [13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%